Protection for Children In Access Maqa Perspective Electronic System - Muhammad Alwi Abidin; Pujangga Candrawijayaning Fajri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The children will be given the next generation who will be competent in advancing the nation, so it is hoped that the children will continue to have good qualities as they grow up. In this modern age, the presence of electronic systems provides an incentive for children to explore themselves further in their growth. However, in addition to having a good impact, electronic systems can also have a negative impact on children when they access features or contents that they should not have access to. Later, with the passage of time, Act No. 1 of 2024 was enacted, which stipulates in Article 16A that electronic system providers, on their features and contents, must provide age warnings for access, verification, and reporting mechanisms for misuse of access to electronic systems. This study is aimed at studying whether it is in accordance with the teaching of maqa>s{id asy-syari>’ah. So in this study, the researchers use the study of library research with a normative approach. As for the results of the study in this research, the load of Article 16A of Law No. 1 of 2024 is inherent with the doctrine of maqa>s{id asy-syari>’ah in the h{ifz{ al-‘aql and h{ifz{ an-nasl, because by limiting his child's access to electronic systems, he will be prevented from accessing features or contents to which he should not have access, so the child's growth will continue to wake up.